2020
DOI: 10.1016/j.vetmic.2019.108491
|View full text |Cite
|
Sign up to set email alerts
|

A virome sequencing approach to feline oral squamous cell carcinoma to evaluate viral causative factors

Abstract: Feline oral squamous cell carcinoma (FOSCC) may be the best naturally-occurring model of human head and neck squamous cell carcinoma (HNSCC). HNSCC can be broadly divided into human papillomavirus (HPV)negative cancers and HPV-positive cancers where HPV is the causative agent. Previous studies in FOSCC have used both species-specific and species-nonspecific PCR primers that may be insensitive to the detection of PVs and other viruses that may be divergent from known sequences. ViroCap is a targeted capture and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 38 publications
4
33
1
Order By: Relevance
“…Due to genetic and behavioral similarities between FcaPV3 and the canine PVs, this PV was classified as the first member of the species 3 Taupapillomaviruses [ 52 ]. This PV has subsequently been detected within hyperplastic and neoplastic skin and oral lesions in cats, suggesting the PV can alter cell regulation [ 53 , 54 , 55 ]. Additionally, lesions that contained FcaPV3 DNA had marked p16 immunostaining suggesting that the virus can degrade pRb [ 53 ].…”
Section: Papillomaviruses That Infect Domestic Catsmentioning
confidence: 99%
“…Due to genetic and behavioral similarities between FcaPV3 and the canine PVs, this PV was classified as the first member of the species 3 Taupapillomaviruses [ 52 ]. This PV has subsequently been detected within hyperplastic and neoplastic skin and oral lesions in cats, suggesting the PV can alter cell regulation [ 53 , 54 , 55 ]. Additionally, lesions that contained FcaPV3 DNA had marked p16 immunostaining suggesting that the virus can degrade pRb [ 53 ].…”
Section: Papillomaviruses That Infect Domestic Catsmentioning
confidence: 99%
“…Even if previous lines of evidence have hypothesized a role of viruses in canine lymphoma ( 56 ), we could not confirm this hypothesis. However, similarly to feline species ( 57 ), studies dedicated to identify viral integration sites in canine cancers are needed, and transmissible venereal tumor and squamous carcinoma represent excellent models to further test VirusFinder2.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, these initial observations were reinforced by multiple reports from different groups and oral infection with high-risk HPV, especially HPV16, was consistently associated with increased HNSCC risk (27)(28)(29). Studies on bovine (30), canine (31), feline (32) and murine (33) models showed the ability of papillomaviruses to infect and induce different types of lesions in the oral cavity, as previously reviewed (34)(35)(36). More recently, our group demonstrated the ability of HPV16 to specifically induce tongue base HNSCC in transgenic mice (37), providing experimental evidence to support the etiologic role of HPV16 in this type of cancer.…”
Section: Hpv-positive Versus Hpv-negative Hnsccmentioning
confidence: 98%